Animality and Forgetfulness in the Second Untimely Meditation (London Journal of Research In Humanities and Social Sciences, 2025)
This article investigates the roles of animality and forgetfulness in Nietzsche’s On the Uses and Disadvantages of History for Life, commonly known as the Second Untimely Meditation. Nietzsche poetically contrasts human historical consciousness with the unhistorical state of animals, which he associates with forgetfulness, immediacy, and happiness. The study explores how these unhistorical elements—especially forgetfulness—are not failures but active forces essential for life and action. It further examines how Nietzsche’s notions of the historical, unhistorical, and suprahistorical evolve in his later works, linking them to his critique of morality and the development of key concepts like the will to power and the overhuman.
Keywords: morality.; history; memory; Nietzsche; animality; forgetfulness; unhistorical; suprahistorical; overhuman